If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7 + -35x + -40 = 11 Reorder the terms: -7 + -40 + -35x = 11 Combine like terms: -7 + -40 = -47 -47 + -35x = 11 Solving -47 + -35x = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '47' to each side of the equation. -47 + 47 + -35x = 11 + 47 Combine like terms: -47 + 47 = 0 0 + -35x = 11 + 47 -35x = 11 + 47 Combine like terms: 11 + 47 = 58 -35x = 58 Divide each side by '-35'. x = -1.657142857 Simplifying x = -1.657142857
| 3l^2-12l-960=0 | | 4x-5-8x=-8 | | x^2-4.36*x=0 | | 8(2x-6)=34 | | 5-(3-P)=7p | | 5-(3-P)=7 | | 6x-2(3x+4)=-20 | | 20p+250=500 | | 3b+38=125 | | -8-32x+8=6 | | 2(x-1)=58 | | 4+19y-2=6y+122-2y | | -8-4(-8x-2)=6 | | 21k^2+91k+98=0 | | .05+.10(2n)=4.20 | | x^4-3x^2+30=0 | | 0=8x^2+6x+3 | | -24x-8-4x=-5 | | 10x^4-x^2-9=0 | | -4x-10k= | | 3(x+2.94)=2x | | 75x^2=3 | | 2m+7-2m+6=x | | 5x+9.16=3x+12 | | 12(3x+6)-7(2x-4)=4x-20 | | 15x-35=8 | | 5x+7=12x-56 | | 32=5x-3 | | -x^4=25-26x^2 | | 15+4a=7a | | -3.8x+1.2=-17.8 | | 35-8=x |